2014
DOI: 10.1186/1471-2393-14-65
|View full text |Cite
|
Sign up to set email alerts
|

Male partner involvements in PMTCT: a cross sectional study, Mekelle, Northern Ethiopia

Abstract: BackgroundMale partner participation is a crucial component to optimize antenatal care/prevention of mother to child transmission of HIV(ANC/PMTCT) service. It creates an opportunity to capture pregnant mothers and their male partners to reverse the transmission of HIV during pregnancy, labour and breast feeding. Thus involving male partners during HIV screening of pregnant mothers at ANC is key in the fight against mother to child transmission of HIV(MTCT). So, the aim of this study is to determine the level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
70
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(90 citation statements)
references
References 13 publications
13
70
7
Order By: Relevance
“…Lastly, our study revealed that, among male partners who accompany their pregnant wives, 117 (95.2%) of husbands who accompany their pregnant wives have tested and counselled for HIV in the current pregnancy of their wives at ANC. This is higher than findings from Mekele and Tanzania [11, 25]. This inconsistency might be due to current improvement in maternal and child health activities when compared to those studies period.…”
Section: Discussioncontrasting
confidence: 61%
“…Lastly, our study revealed that, among male partners who accompany their pregnant wives, 117 (95.2%) of husbands who accompany their pregnant wives have tested and counselled for HIV in the current pregnancy of their wives at ANC. This is higher than findings from Mekele and Tanzania [11, 25]. This inconsistency might be due to current improvement in maternal and child health activities when compared to those studies period.…”
Section: Discussioncontrasting
confidence: 61%
“…Less than 1% of male partners were tested in the PPTCT clinic; the proportion had significantly reduced over the past 10 years. Though, low male involvement has been reported globally,[20212223] none of these studies found the involvement to be as low as our study. In general, HIV testing among male partners has been reported to be significantly higher in HIV-infected women and in those whose men who had tested for HIV earlier.…”
Section: Discussioncontrasting
confidence: 83%
“…Various socio-cultural factors may influence the involvement of the husband in pregnancy and child birth. Comprehensive strategies to sensitize and advocate the importance of the male partner/husband are to be put in place [28] as a part of the training programme.…”
Section: Discussionmentioning
confidence: 99%